2018
DOI: 10.2174/1389200219666171207121313
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondrial Mechanism in Chemotherapy-Induced Peripheral Neuropathy

Abstract: The pathophysiology of CIPN is complicated as chemotherapeutic medications often involve combination of drugs. With these combinatorial therapies cancer survivors develop continuing effects of CIPN which require rehabilitation strategies for the recovery of patient's condition and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 0 publications
1
30
0
1
Order By: Relevance
“…It is important to speculate that OXAL-induced stimulation of MEP-induced channels presented herein contributes to its activation of mitochondrial permeability transition pore. Our results are in parallel with a scenario showing the role of mitochondrial mechanism in platinum-induced peripheral neuropathy [55,56]. It remains to be studied to what extent the presence of OXAL can enhance MEP-elicited channels which indirectly activate the intrinsic pathway to apoptotic or necrotic changes by inducing change in mitochondrial permeability transition pore.…”
Section: Discussionsupporting
confidence: 82%
“…It is important to speculate that OXAL-induced stimulation of MEP-induced channels presented herein contributes to its activation of mitochondrial permeability transition pore. Our results are in parallel with a scenario showing the role of mitochondrial mechanism in platinum-induced peripheral neuropathy [55,56]. It remains to be studied to what extent the presence of OXAL can enhance MEP-elicited channels which indirectly activate the intrinsic pathway to apoptotic or necrotic changes by inducing change in mitochondrial permeability transition pore.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have shown the important role of oxidative stress in the toxicity of oxaliplatin [ 11 , 37 , 51 53 ]. An excessive production of ROS can alter endothelial cells integrity by cytoskeletal rearrangements and redistribution of TJ proteins, triggering a loss of cellular interaction and increasing their permeability [ 54 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies with cycling cells in cell culture and cisplatin were done in the past; the toxic effects of cisplatin on cells were associated with the formation of platinum-DNA adducts as well as damage to other cellular components and organelles—from mitochondria to axonal transport (Avan et al 2015 ; Boyette-Davis et al 2015 ; Canta et al 2015 ; Carozzi et al 2015 ; Chiorazzi et al 2015 ; Foufelle and Fromenty 2016 ; Kanat et al 2017 ; Kerckhove et al 2017 ; McDonald et al 2005 ; Nicolini et al 2015 ; Starobova and Vetter 2017 ; Waseem et al 2018 ). In order to investigate the subcellular location of platinum in cisplatin-exposed NT2-N cells, we chose to use X-ray fluorescence microscopy (XFM)—the only imaging technique that can be used for direct visualization and quantification od chemical elements, native to cells or exogenously introduced into them (Bourassa et al 2014 ; Kim et al 2010 ; Paunesku et al 2006 , 2012 ; Wang et al 2014 ; Weekley et al 2013 ; Wolford et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of cisplatin on living cells are generally considered to be associated with genomic and mitochondrial DNA damage and the creation of DNA adducts (Chiorazzi et al 2015 ; Johnstone et al 2016 ; Kanat et al 2017 ; Starobova and Vetter 2017 ; Wang and Lippard 2005 ) but its side-effects are often associated with oxidative stress (Mercantepe et al 2018 ; Wang et al 2018 ). Oxidative stress, nitro-oxidative stress and mitochondrial impairment are often noted as possible factors in the etiology of cisplatin-induced neuronal injury (Areti et al 2014 ; Carozzi et al 2010 ; Ma et al 2018 ; Maj et al 2017 ; Waseem et al 2018 ). Many different agents have been tested as possible interventions (Albers et al 2014 ; Avan et al 2015 ; Freyer et al 2017 ; Fu et al 2017 ; Glimelius et al 2018 ; Kerckhove et al 2017 ; Mishra and Alsbeih 2017 ; Piccolo and Kolesar 2014 ; Schloss et al 2013 ), but a clear view of their mechanism of action is still lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation